Disturbing the activity of the primary motor cortex by means of transcranial magnetic stimulation affects long term memory of sentences referred to manipulable objects - Vitale, Francesca; de Vega, Manuel (Frontiers in Psychology, 2023)
Introduction Previous studies on embodied meaning suggest that simulations in the motor cortex play a crucial role in the processing of action sentences. However, there is little evidence that embodied meaning have functional impact beyond working memory. This study examines how the neuromodulation of the motor cortex (M1) could affect the processing of action-related language, measuring participants’ performance in a long-term memory task. Method Participants were submitted to two sessions in separate days, one with low-frequency repetitive transcranial magnetic stimulation (rTMS) and the other with sham rTMS. The pulses were delivered for 15 minutes over M1 or over V1, used as a control area. After each stimulation or sham period, the participants were asked to memorize a list of simple sentences, with a manual action verb or an attentional verb, followed in both cases by a noun referred to a manipulable object (e.g., to hang a cane vs. to observe a cane). Finally, they received the verbs as cues with instructions to recall the nouns. Results The results showed that low frequency rTMS on M1, compared to sham stimulation, significantly improved the performance in the memory task, for both types of sentences. No change in performance was found after the rTMS stimulation of V1. Discussion These results confirm that the perturbation on the motor system, affect the memory of manipulable object names in the context of sentences, providing further evidence of the role played by the sensorimotor system in the encoding and recall of concrete sentences of action.